Reactivity of industrial wastes as measured through ICP‐OES: A case study on siliceous Indian biomass ash. Issue 12 (19th June 2019) - Uvegi, Hugo; Chaunsali, Piyush; Traynor, Brian; Olivetti, Elsa
Abstract: An untapped source of amorphous SiO2, industrially generated Indian biomass ash (SA)—90% amorphous, with composition of 60% SiO2 and 20% unburnt carbon—can be used to produce cementitious and alkali‐activated binders. This study reports dissolution of amorphous Si from SA in 0.5 mol/L and 1 mol/L aqueous NaOH, with and without added Ca(OH)2, at SA:Ca(OH)2 wt% ratios of 100:0, 87.5:12.5, and 82.5:17.5. Monitoring of elemental dissolution and subsequent/simultaneous product uptake by ICP‐OES offers an effective process for evaluating utility of industrial wastes in binder‐based systems. After 28 days in solution, up to 68% of total Si is dissolved from SA in 1 mol/L NaOH, with values as much as 38% lower in the presence of Ca(OH)2, due to the formation of tobermorite‐like C‐S‐H. FTIR, 29 Si MAS‐NMR, and XRD are used to characterize solid reaction products and observe reaction progress. Product chemistries calculated from ICP‐OES results and verified by selective dissolution in EDTA/NaOH—namely, Ca/Si of 0.6‐1 and Na adsorption of 1‐2 mmol/g—are found to be consistent with those indicated by aforementioned techniques. This indicates the efficacy of ICP‐OES in estimating product chemistry via such a methodology.